Categories at al-Farabi, what are they? - Al-Daly, Raedah (Journal of Oriental Studies, 2020)
The Categories took root with the Arab philosopher Abu Ishaq Yaqoub al-Kindi as one of the most important logical, philosophical and linguistic investigations. And before al-Farabi’s works the understanding of the Categories, the basis for the acquisition of logical and philosophical knowledge was not completed. Abu Nasr Al-Farabi, who was a student of Bishr Matta bin Yunus, and took the making of logic from Yuhanna Ibn Haylan, was the first to develop the science of Aristotelian logic in its comprehensive and detailed form. Al-Farabi became the first teacher for those who wanted to stand on the truth of Aristotelian logic, and to understand the meaning of Categories, and how they are the firsts established for all sciences The text of al-Farabi was the mayor in Ibn Baja’s philosophy in Andalusia. The main goal and purpose of this study is to try understanding the Categories in the thought of Abu Nasr al-Farabi, by arranging the al-Farabi texts that dealt with this topic, in an attempt to reveal his understanding of the Categories, and to try to answer the question of what is the purpose of the Categories. He made of logic a race that includes three types, the first is linguistic logic, the second is philosophical logic, and the third is intellectual logic, making the strength of the soul the bearer of this logic, this power which is the utterance and from which the name of logic is derived. Since the goal of philosophy is to reach the final perfection, and to reach the truth, which is the ultimate happiness, and proof was the conductor of truth and certainty, according to Al-Farabi, the Categories were the bearer of this perfection by force, as the proof material was twice, the first being the material for proof in terms of words, and in the second the material for proof in terms of meanings, and the last being the purpose. Key words: philosophy, logic, categories, intelligibles, sayings, Aristotle, al-Farabi.